Pengembangan Perangkat Pembelajaran Fisika Berbasis Inkuiri Terbimbing untuk Melatihkan Keterampilan Berpikir Kreatif Siswa - Widia, Widia; Soetjipto, Soetjipto; Ibrahim, Muslimin; Sarnita, Fitria; Saifullah, Saifullah (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2024)
Creative thinking skills are one of the skills that are very necessary in the 21st century, so it is important to train students. This research aims to develop a guided inquiry-based physics learning tool that is suitable for practicing creative thinking skills on static fluid material in SMA/MA. This research is development research using a 4-D model with an experimental type of research with a one-group pretest-posttest design. The learning tools developed include; (1) Learning Implementation Plan; (2) Student textbooks; and (3) Student Activity Sheet. Data collection techniques use tests, observation, and documentation using creative thinking skills test instruments, student activity observation sheets, and student response questionnaires. This research was conducted on 22 class XI students. Data analysis techniques use quantitative and qualitative descriptive to test the validity, practicality, and effectiveness of the data. The research findings are: 1) The learning tools developed are categorized as valid; 2) The practicality of learning tools can be seen from the implementation of the learning implementation plan and student activities carried out in accordance with the planned stages; 3) The effectiveness of learning tools is seen from (a) Students' creative thinking skills before being given treatment and after being given treatment, (b) Students' responses to the tools and implementation of learning. So it can be concluded that the guided inquiry-based physics learning tool developed is suitable for training students' creative thinking skills.